Analytical sensitivity of a method is critical in detection of low-level BRCA1 constitutional epimutation - Filip Machaj; Katarzyna Ewa Sokolowska; Konrad Borowski; Szymon Retfiński; Dominik Strapagiel; Marta Sobalska-Kwapis; Tomasz Huzarski; Jan Lubiński; Tomasz Kazimierz Wojdacz (Scientific Reports, 2023)
Abstract Recent reports based on a substantial number of cases, warrant need for population-based research to determine implications of constitutional methylation of tumor suppressor genes such as BRCA1 occurring in healthy tissue in the prediction of cancer. However, the detection of the constitutional methylation in DNA extracted from blood has already been shown to be technologically challenging, mainly because epimutations appear to be present in blood at a very low level. The analytical sensitivity required for low-level methylation detection can be provided by NGS, but this technique is still labor and cost-intensive. We assessed if PCR-based MS-HRM and BeadChip microarray technologies, which are standardized and cost-effective technologies for methylation changes screening, provide a sufficient level of analytical sensitivity for constitutional BRCA1 methylation detection in blood samples. The study included whole blood samples from 67 healthy women, 35 with previously confirmed and 32 with no detectable BRCA1 promoter methylation for which we performed both MS-HRM based BRCA1 gene methylation screening and genome wide methylation profiling with EPIC microarray. Our results shown, that low-level BRCA1 methylation can be effectively detected in DNA extracted from blood by PCR-based MS-HRM. At the same time, EPIC microarray does not provide conclusive results to unambiguously determine the presence of BRCA1 constitutional methylation in MS-HRM epimutation positive samples. The analytical sensitivity of MS-HRM is sufficient to detect low level BRCA1 constitutional epimutation in DNA extracted from blood and BeadChip technology-based microarrays appear not to provide that level of analytical sensitivity.